Epidemiologia i profilaktyka raka piersi = Epidemiology and prophylaxis of breast cancer - Bojakowska, Urszula Jolanta; Kalinowski, Paweł; Kowalska, Marta (Journal of Education, Health and Sport, 2016)
Bojakowska Urszula, Kalinowski Paweł, Kowalska Marta Estera. Epidemiologia i profilaktyka raka piersi = Epidemiology and prophylaxis of breast cancer. Journal of Education, Health and Sport. 2016;6(8):701-710. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61187 http://ojs.ukw.edu.pl/index.php/johs/article/view/3799 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016. Epidemiologia i profilaktyka raka piersi Epidemiology and prophylaxis of breast cancer Urszula Bojakowska1,2, Paweł Kalinowski1, Marta Estera Kowalska1 1. Samodzielna Pracownia Epidemiologii Uniwersytet Medyczny w Lublinie 2. SKN przy Samodzielnej Pracowni Epidemiologii, Uniwersytet Medyczny w Lublinie Słowa kluczowe: rak piersi, epidemiologia, profilaktyka. Key words: brest cancer, epidemiology, prophylaxis. Streszczenie W ostatnich latach natężenie chorób nowotworowych zwiększyło się szczególnie. Rak piersi stanowi obecnie jeden z największych problemów epidemiologicznych. Ze względu na fakt, że rak piersi tak często prowadzi do zgonu, należałoby włożyć więcej wysiłku we wczesne wykrywanie. Bezwzględnie rak piersi wymaga skutecznych działań w zakresie profilaktyki oraz edukacji społeczeństwa. Celem pracy było przedstawianie epidemiologii oraz metod profilaktyki raka piersi. Abstract In recent years, the intensity of cancers particularly increased. Breast cancer is one of the greatest epidemiological problem at present. Due to the fact that breast cancer so often leads to death that should be more efforts in the early detection. Absolutely breast cancer requires effective actions in the prevention and education of the society in this respect. The aim of the study was to present the epidemiology and methods of breast cancer prophylaxis.